Optimizing Optogenetic Activation of Purkinje Cell Axons to Investigate the Purkinje Cell – DCN Synapse - Gruver, Kim M.; Watt, Alanna J. (Frontiers in Synaptic Neuroscience, 2019)
Optogenetics is a state-of-the-art tool for interrogating neural circuits. In the cerebellum, Purkinje cells serve as the sole output of the cerebellar cortex where they synapse on neurons in the deep cerebellar nuclei (DCN). To investigate the properties of this synaptic connection, we sought to elicit time-locked single action potentials from Purkinje cell axons. Using optical stimulation of channelrhodopsin-2 (ChR2)-expressing Purkinje cells combined with patch-clamp recordings of Purkinje cells and DCN neurons in acute cerebellar slices, we determine the photostimulation parameters required to elicit single time-locked action potentials from Purkinje cell axons. We show that axons require longer light pulses than somata do to elicit single action potentials and that Purkinje cell axons are also more susceptible to light perturbations. We then demonstrate that these empirically-determined photostimulation parameters elicit time-locked synaptic currents from postsynaptic cells in the DCN. Our results highlight the importance of optimizing optogenetic stimulation conditions to interrogate synaptic connections.